Rehabilitating the old thinkers for a Linguistics in the 21st century - Fortes, Fábio (Proaera-UFRJ, 2016)
Historical perspective has been recently revalued by the field of Linguistics. However, the appropriation of past elements in order to make a sort of ‘History of this discipline' has not always been carried out taking into account any methodological and theoretical aspects involving the reading of an ancient text. In this paper, we aim at giving our contribution to designing some methodological and theoretical aspects which must come out  whenever dealing with metalinguistic treatises from ancient times, as well as reflecting on possible contributions that the Classical Studies can effectively provide to the Historiography of Linguistics.